THE FALL OF THE ANGELS ACCORDING TO ST. AUGUSTINE (Годишен зборник на Филозофски факултет - Скопје, 2025)
Considering the substantial impact of St. Augustine’s stances on the evil inthe world, the status and the actions of the devil, and the dangers of collaborating (orcompacting) with the dark forces on the development of the medieval theology of violentreckoning against the evil, this text examines one aspect of his use of the motif of the fallof the angels in the analysis of the problem and the proliferation of evil. As one of the lastearly Christian authors who uses elements from the story from the Biblical tradition andthe tradition around the fallen Watchers from the First Book of Enoch, St. Augustineapproaches the problem of evil from the standpoint of the importance of free choice andof the intentional transgression. The text first offers a brief overview of the conceptionof the evil in the Manichean cosmogony, in order to introduce the positions to which St.Augustine explicitly opposes. The important role of the primordial sin according to himis shown, and especially, the status of the devil as a sinner from the beginning, or as aself-determined rebel against God.Тhe ideas on the origin of evil through the role of the satan are outlined throughSt. Augustine’s polemic against the Manicheans. The majority of the text is devoted tothe problem of the angelic (non)blessedness. St. Augustine’s position on the existenceof two groups of heavenly beings (good and evil) is shown, as is the idea about theawareness, or foreknowledge, of a potentially undisturbed eternal bliss, as opposed to theignorance (or the foreknowledge) about the loss of this perennial happiness as a result ofthe intentional apostasy of the bad angels. These few aspects of St. Augustine’s complextheology trace his underlying position on the importance of the conscious choice to constantlybe(come) better and to imitate God, despite man’s initial sinfulness.